2016
DOI: 10.1523/jneurosci.4317-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-Derived Macrophages Contribute to Spontaneous Long-Term Functional Recovery after Stroke in Mice

Abstract: Stroke is a leading cause of disability and currently lacks effective therapy enabling long-term functional recovery. Ischemic brain injury causes local inflammation, which involves both activated resident microglia and infiltrating immune cells, including monocytes. Monocyte-derived macrophages (MDMs) exhibit a high degree of functional plasticity. Here, we determined the role of MDMs in longterm spontaneous functional recovery after middle cerebral artery occlusion in mice. Analyses by flow cytometry and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
265
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(296 citation statements)
references
References 71 publications
16
265
2
3
Order By: Relevance
“…Some of the most intriguing data that have emerged from the field of neuroimmunology indicate that in the context of CNS injury, T effector cells and even monocytes can traffic to the brain and induce repair processes that have a significant impact on the extent of tissue damage and destruction (Schwartz and Shechter, 2010;Wattananit et al, 2016). For example, after partial crush injury of the optic nerve, T cells immunized to specific CNS antigens (ie, myelin basic protein) were found to protect against secondary nerve degeneration (Moalem et al, 1999).…”
Section: Immunological Mechanismsmentioning
confidence: 99%
“…Some of the most intriguing data that have emerged from the field of neuroimmunology indicate that in the context of CNS injury, T effector cells and even monocytes can traffic to the brain and induce repair processes that have a significant impact on the extent of tissue damage and destruction (Schwartz and Shechter, 2010;Wattananit et al, 2016). For example, after partial crush injury of the optic nerve, T cells immunized to specific CNS antigens (ie, myelin basic protein) were found to protect against secondary nerve degeneration (Moalem et al, 1999).…”
Section: Immunological Mechanismsmentioning
confidence: 99%
“…A recent study also supports the view of macrophage conversion at the injury site. Wattananit et al [117] showed a beneficial role for early recruited CCR2 + monocyte-derived macrophages on functional recovery through enhancing resolution of inflammation. While there have been advances in understanding the role of mononuclear phagocytes in stroke, defining the phenotype of mononuclear phagocytes relevant to their function in the poststroke brain has been understudied.…”
Section: Macrophage Polarization In Strokementioning
confidence: 99%
“…Аналогичные данные получены Gliem M. и соавт., которые продемонстрировали, что провоспалительные моноциты быстро рекру-тируются в зону ишемии через CCR2-зависимый путь и дифференцируются в макрофаги, обеспе-чивающие нейропротекцию и нейроваскулярную репарацию в зоне ишемии [37]. Стимулирующий эффект рекрутируемых макрофагов на невроло-гическое восстановление в отдаленном перио-де инсульта продемонстрирован недавно [129]. Авторы показали, что на 7 сутки после инсульта половина рекрутируемых макрофагов экспрес-сирует М2-, а половина -М1-фенотип.…”
Section: продукция провоспалительных медиаторовunclassified